Coexistence of Alzheimer’s disease with pseudoexfoliation syndrom PEX - Reniewska, Barbara; Mulak, Małgorzata; Misiuk-Hojło, Marta; Kostuś, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica, 2004)
Alzheimer disease is a type of cerebral amyloidosis, which is most frequently recognized after the age of 80. In pathophysiology of Alzheimer's disease, Parkinson's disease, amyotrophic lateral sclerosis and age-related cataract changes in protein aggregation play important role, for that reason they form common group of diseases, called conformational diseases. Patients with Alzheimer disease have more common pseudoexfoliation syndrom (PEX), characterized by the accumulation of an abnormal pathognomonic material in the anterior segment of the eye. Regarding common feature of the structure of fibrillar pseudoexfoliation and amyloid material, it is considered that eye examination could be useful in the early diagnosis of Alzheimer disease.